The perceived fair duration of unemployment benefits for older workers. The role of lifetime achievements in the labour market - Monika Senghaas; Christopher Osiander; Gesine Stephan; Olaf Struck; Richard Wolff (International Journal of Social Welfare, 2022)
The welfare state regulates social policies and reallocates scarce resources. For the social legitimacy of the welfare state, it is important that the public supports the principles underlying this reallocation. This article examines the impact of different activities during the life course on public deservingness perceptions of older unemployed people. In a factorial survey experiment conducted among a random sample of individuals drawn from German administrative employment records, we examine the maximum duration of benefit receipt which is perceived as fair for older unemployed persons with different biographies. The results indicate strong public support for a nexus between previous contributions and benefit entitlements. Besides financial contributions to unemployment insurance, parenting and further training are considered to be `lifetime achievements' which justify longer unemployment benefit receipt. We interpret these findings as an expression of a generalised form of reciprocity which guides perceptions of deservingness regarding older unemployed persons.
Keywords: 330; deservingness; factorial survey; Germany; maximum benefit duration; unemployment insurance